Hydrophobic battery plate and preparation method thereof
By applying PTFE binder to the surface of the conductive paste layer of the battery plate and forming a hydrophobic layer, the problem of insufficient bonding strength between the conductive paste layer and the current collector is solved, and the service life and performance stability of the battery are significantly improved.
Patent Information
- Application Number
- CN202411812377.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-04
AI Technical Summary
The bonding strength between the conductive paste layer and the current collector in the existing battery plate is poor, resulting in problems such as voltage drop, short circuit and shortening of cycle life during use of the battery.
By additionally applying PTFE binder to the surface of the conductive paste layer and forming a hydrophobic layer after drying, the bond strength between the conductive paste layer and the current collector is improved.
Effectively prevent the electrolyte from infiltrating and corrosion on the conductive paste layer, maintain a firm combination between the conductive paste layer and the current collector, and avoid degradation of battery performance.
Smart Images

Figure BDA0005180848300000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery plates, and in particular to a hydrophobic battery plate and a preparation method thereof. Background Art
[0002] Batteries, as devices that convert chemical energy into electrical energy, have been widely used in power tools, hybrid vehicles, energy storage systems, portable electronic devices and other fields since their birth due to their high energy density, long life, environmental friendliness and excellent cycle memory characteristics.
[0003] Batteries are usually composed of core components such as positive plates, negative plates, electrolytes, diaphragms and shells. Among them, the performance of battery plates (positive plates and negative plates) plays an important role in the overall performance of the battery. Battery plates usually include a current collector and a conductive slurry layer obtained by coating a conductive slurry on the current collector and curing it. The conductive slurry usually includes active substances, conductive agents and binders. The active substances, as the core of the chemical reaction, directly determine the capacity and energy density of the battery. The binder can adhere the conductive slurry layer to the surface of the current collector to ensure the stable performance of the battery.
[0004] However, in actual applications, when the electrolyte is in direct contact with the conductive paste layer, especially when the electrolyte containing water and other wet components is in direct contact with the conductive paste layer, it will have a significant infiltration and corrosion effect on the conductive paste layer. Long-term infiltration and corrosion cause the conductive paste layer to gradually present a "mud" state, thereby weakening the bonding strength between the conductive paste layer and the current collector. Even if the binder is designed to enhance the adhesion between the conductive paste layer and the current collector, the conductive paste layer is still easy to fall off from the surface of the current collector under the long-term infiltration and corrosion of the electrolyte, resulting in a series of problems such as voltage drop, short circuit and shortened cycle life of the battery during use.
[0005] In response to the above technical difficulties, the industry currently generally attempts to add a hydrophobic protective layer on the surface of the conductive slurry layer through physical surface modification technology (such as laser treatment, ion implantation, etc.) or chemical surface modification technology (such as chemical vapor deposition, sol-gel method, etc.). The purpose of these protective layers is to prevent the electrolyte from directly contacting the conductive slurry layer, thereby reducing the infiltration and corrosion of the conductive slurry layer by the electrolyte, and then enhancing the bonding strength between the conductive slurry layer and the current collector surface. However, the effect of the above approach is limited by the choice of raw materials, resulting in limited improvement in the bonding strength between the conductive slurry layer and the current collector in the battery plate, which is difficult to meet actual application requirements; in addition, physical surface modification technology and chemical surface modification technology usually require more complex equipment and operating procedures, and have higher requirements for the control of process parameters. This not only increases the complexity of preparation, but also increases the cost, making it difficult to achieve industrial application. Summary of the invention
[0006] One of the purposes of the present invention is to propose a method for preparing a hydrophobic battery plate, which is beneficial to improve the bonding strength between the conductive slurry layer and the current collector while simplifying the preparation method and reducing the production cost, and avoid problems such as voltage drop, short circuit and shortened cycle life during the use of the battery, so as to overcome the shortcomings of the prior art.
[0007] The second purpose of the present invention is to provide a hydrophobic battery plate, which is beneficial to improve the bonding strength between the conductive slurry layer and the current collector, thereby solving the problems of voltage drop, short circuit and shortened cycle life that occur during the use of the battery.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] A method for preparing a hydrophobic battery plate comprises the following steps:
[0010] A. stirring the active material, the conductive agent and the solvent to obtain a first mixture; adding a PTFE binder to the first mixture, stirring and filtering to obtain a conductive slurry;
[0011] B. filling the conductive slurry into a current collector having a porous structure, and then drying and compacting the current collector to obtain a conductive slurry layer;
[0012] C. Coating a PTFE binder on the surface of the conductive slurry layer, and forming a hydrophobic layer after drying to obtain a hydrophobic battery plate.
[0013] Furthermore, in step A, the content of PTFE binder in the conductive paste is 1-7% calculated by mass percentage.
[0014] Furthermore, in step A, the filtration screen has a mesh size of 20 to 60.
[0015] Furthermore, step B specifically comprises: filling the conductive slurry into the current collector having a porous structure, and sequentially performing rapid drying, slow drying and compacting to obtain a conductive slurry layer;
[0016] The drying temperature of the rapid drying is 160-180°C, and the drying time is 10-15s;
[0017] The drying temperature of the slow drying is 140-155° C., and the drying time is 20-40 seconds;
[0018] The compaction pressure is 210-400T, and the time is 5-10s.
[0019] Furthermore, in step B, the thickness of the conductive paste layer is 0.4-0.6 mm.
[0020] Furthermore, in step B, the current collector having a porous structure is any one of a foam nickel substrate, a honeycomb nickel substrate and a copper foam substrate.
[0021] Furthermore, in step C, the drying temperature is 170-185° C., and the drying time is 20-35 seconds.
[0022] Furthermore, in step C, the thickness of the hydrophobic layer is 0.001 to 0.01 mm.
[0023] A hydrophobic battery plate is prepared using the above-mentioned method for preparing the hydrophobic battery plate.
[0024] The technical solution provided by the present invention may include the following beneficial effects:
[0025] 1. The three-dimensional network structure formed by the PTFE binder can tightly wrap the conductive paste layer formed after the conductive paste is dried and solidified, and form a good combination with the current collector, so that the conductive paste layer can be firmly anchored on the current collector.
[0026] 2. The molecular chain of PTFE is composed of closely arranged carbon atoms and fluorine atoms, forming a unique spiral structure. The above structure not only enhances the interaction force between PTFE molecules, but also gives its surface extremely high smoothness and difficult-to-penetrate properties. In addition, the high proportion of fluorine atoms in PTFE molecules further reduces its surface energy, thereby enhancing its hydrophobic properties. Therefore, after drying and curing, the conductive paste with the addition of PTFE binder can form a conductive paste layer with excellent hydrophobicity, thereby effectively preventing the infiltration and corrosion of the conductive paste layer by moisture or other wet components in the electrolyte, and avoiding the conductive paste layer from "mudification" due to long-term infiltration and corrosion of the electrolyte, thereby maintaining a firm bond between the conductive paste layer and the current collector.
[0027] 3. This technical solution additionally applies a layer of PTFE binder on the surface of the conductive paste layer, and forms a hydrophobic layer after drying. The above-mentioned hydrophobic layer not only serves as a protective layer to effectively prevent the direct contact between the electrolyte and the conductive paste layer, but also because of its low surface energy characteristics, it makes it difficult for the electrolyte to spread and penetrate on the surface of the battery plate, further reducing the risk of the conductive paste layer being infiltrated and corroded, thereby improving the bonding strength between the conductive paste layer and the current collector. At the same time, due to the bonding properties of the PTFE binder, the hydrophobic layer formed after the PTFE binder is dried and solidified is also conducive to anchoring the conductive paste layer more firmly on the current collector, which is also conducive to improving the bonding strength between the conductive paste layer and the current collector. In addition, the PTFE binder has extremely high chemical stability and can resist the erosion of chemical substances such as acids, alkalis, oxidants and reducing agents. The hydrophobic layer formed after the PTFE binder is dried and solidified can protect the conductive paste layer to better resist the corrosion of the electrolyte, and is also conducive to improving the bonding strength between the conductive paste layer and the current collector. DETAILED DESCRIPTION
[0028] The present technical solution provides a method for preparing a hydrophobic battery plate, comprising the following steps:
[0029] A. stirring the active material, the conductive agent and the solvent to obtain a first mixture; adding a PTFE binder to the first mixture, stirring and filtering to obtain a conductive slurry;
[0030] B. filling the conductive slurry into a current collector having a porous structure, and then drying and compacting the current collector to obtain a conductive slurry layer;
[0031] C. Coating a PTFE binder on the surface of the conductive slurry layer, and forming a hydrophobic layer after drying to obtain a hydrophobic battery plate.
[0032] In order to overcome the technical problems of poor bonding strength between the conductive slurry layer and the current collector surface in existing battery plates, and complex and high-cost preparation methods of battery plates, the present technical solution proposes a preparation method for hydrophobic battery plates, which is beneficial to improving the bonding strength between the conductive slurry layer and the current collector while simplifying the preparation method and reducing production costs, thereby avoiding problems such as voltage drop, short circuit and shortened cycle life during battery use.
[0033] Specifically, in the present technical solution, a PTFE binder is added to the conductive paste. The three-dimensional network structure formed by the PTFE binder can tightly wrap the conductive paste layer formed after the conductive paste is dried and solidified, and form a good bond with the current collector, so that the conductive paste layer can be firmly anchored on the current collector.
[0034] At the same time, the molecular chain of PTFE is composed of carbon atoms and fluorine atoms arranged closely, forming a unique spiral structure. The above structure not only enhances the interaction force between PTFE molecules, but also gives its surface extremely high smoothness and difficult to penetrate characteristics. In addition, the high proportion of fluorine atoms in PTFE molecules further reduces its surface energy, thereby enhancing its hydrophobic properties. Therefore, after drying and curing, the conductive paste added with PTFE binder can form a conductive paste layer with excellent hydrophobicity, thereby effectively preventing the moisture or other wet components in the electrolyte from infiltrating and corroding the conductive paste layer, avoiding the conductive paste layer from being "mudified" due to long-term infiltration and corrosion of the electrolyte, thereby maintaining the firm combination between the conductive paste layer and the current collector. That is, the technical solution cooperates with each other in terms of the bonding effect and hydrophobic effect of the PTFE binder, thereby improving the bonding strength between the conductive paste layer and the current collector.
[0035] Although the type of preferred binder is conducive to improving the bonding strength between the conductive paste layer and the current collector, the degree of improving the bonding strength between the conductive paste layer and the current collector by adding PTFE binder to the conductive paste alone is limited, and it is difficult to meet the use requirements of extremely high bonding strength between the conductive paste layer and the current collector. In order to meet the use requirements of extremely high bonding strength, the present technical solution additionally applies a layer of PTFE binder on the surface of the conductive paste layer, and forms a hydrophobic layer after drying. The above-mentioned hydrophobic layer not only serves as a protective layer to effectively prevent the direct contact between the electrolyte and the conductive paste layer, but also because of its low surface energy characteristics, it is difficult for the electrolyte to spread and penetrate on the surface of the battery plate, further reducing the risk of the conductive paste layer being infiltrated and corroded, thereby improving the bonding strength between the conductive paste layer and the current collector. At the same time, due to the bonding properties of the PTFE binder, the hydrophobic layer formed after the PTFE binder is dried and solidified is also conducive to anchoring the conductive paste layer more firmly on the current collector, which is also conducive to improving the bonding strength between the conductive paste layer and the current collector. In addition, PTFE binder has extremely high chemical stability and can resist corrosion from chemical substances such as acid, alkali, oxidant and reducing agent. The hydrophobic layer formed after the PTFE binder is dried and solidified can protect the conductive paste layer and better resist corrosion from the electrolyte, and is also conducive to improving the bonding strength between the conductive paste layer and the current collector. Therefore, based on the above characteristics of the PTFE binder, the hydrophobic layer formed after the PTFE binder is dried and solidified can greatly improve the bonding strength between the conductive paste layer and the current collector.
[0036] Therefore, the technical solution significantly improves the bonding strength between the conductive paste layer and the current collector by optimizing the type of binder and adding a hydrophobic layer to the conductive paste layer, avoiding the voltage drop, short circuit and shortened cycle life that may occur during the use of the battery, thereby ensuring the stability of the battery performance. At the same time, compared with the method of using physical surface modification or chemical surface modification in the prior art to improve the bonding strength between the conductive paste layer and the current collector, the technical solution abandons the complex equipment and cumbersome operation process, and reduces the strict control requirements for process parameters, making the preparation method of the technical solution simple, low in production cost, and easy to achieve large-scale production.
[0037] It should be noted that although PVDF binder is also widely used in the field of battery plates, the overall molecular structure of PVDF is relatively loose, which limits its hydrophobic properties to a certain extent. Therefore, PVDF binder is not suitable for this technical solution.
[0038] In addition, the manufacturer of the PTFE binder used in this technical solution is Shanghai Huayi Sanaifu New Materials Co., Ltd., and the model is PR301B. In addition, the specific types of active materials, conductive agents and solvents are not limited in this technical solution, and can be flexibly selected according to actual needs. For example, the active material can be selected from lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide or nickelous hydroxide, etc.; the conductive agent can be selected from carbon black, graphite, nickel powder or carbon nanotubes, etc.; the solvent can be selected from N-methylpyrrolidone, dimethyl carbonate or diethyl carbonate, etc.
[0039] Further, in step A, the content of PTFE binder in the conductive paste is 1-7% calculated by mass percentage.
[0040] By limiting the content of PTFE binder in the conductive slurry, it is beneficial to ensure the performance of the battery plate at a lower cost.
[0041] Further description, in step A, the mesh size of the filtration is 20 to 60 meshes.
[0042] By limiting the mesh size of the filter, it is beneficial to remove impurities in the conductive slurry while maintaining the fluidity of the conductive slurry, thereby ensuring the performance of the battery plate.
[0043] Further, step B specifically comprises: filling the conductive slurry into a current collector having a porous structure, and sequentially performing rapid drying, slow drying and compacting to obtain a conductive slurry layer;
[0044] The drying temperature of the rapid drying is 160-180°C, and the drying time is 10-15s;
[0045] The drying temperature of the slow drying is 140-155° C., and the drying time is 20-40 seconds;
[0046] The compaction pressure is 210-400T, and the time is 5-10s.
[0047] Rapid drying removes the solvent in the conductive paste to prevent rolling during the subsequent compaction process, which affects the flatness and quality of the final product. Slow drying further removes the solvent in the conductive paste layer, reducing the solvent content in the conductive paste to less than 2%, which is also beneficial to ensure the performance and stability of the final product.
[0048] Furthermore, by optimizing the pressure and time in the compaction step, it is possible not only to ensure that the conductive slurry layer of the expected thickness is obtained, thereby ensuring the performance of the product, but also to avoid damage to the active material during the compaction process, thereby ensuring the performance of the battery.
[0049] It should be noted that the compaction step of the present technical solution adopts a double-roll calender, and the gap width between the two rollers in the double-roll calender is 0.1 to 0.3 mm.
[0050] Further, in step B, the thickness of the conductive paste layer is 0.4-0.6 mm.
[0051] The thickness of the conductive paste layer directly affects the energy density, cycle life and manufacturing cost of the battery obtained by using the battery plate. In addition, when the conductive paste layer is too thick, it is also easy to affect the bonding strength between the conductive paste layer and the current collector. Therefore, the technical solution limits the thickness of the conductive paste layer, which is beneficial to ensure not only the bonding strength between the conductive paste layer and the current collector at a lower cost, but also the energy density and cycle life of the battery obtained by using the battery plate.
[0052] Further, in step B, the current collector having a porous structure is any one of a foam nickel substrate, a honeycomb nickel substrate and a copper foam substrate.
[0053] The technical solution optimizes the types of current collectors with porous structures. On the one hand, the above-mentioned types of current collectors have better electrical properties and higher power, which is beneficial to ensuring the performance of battery plates. On the other hand, it is also beneficial to select current collectors with porous structures according to actual needs, thereby improving the flexibility of the preparation method.
[0054] Further description, in step C, the drying temperature is 170-185° C., and the drying time is 20-35 seconds.
[0055] By limiting the drying temperature and time, while ensuring the performance of the PTFE binder, not only can the PTFE binder form a uniform hydrophobic layer, which is beneficial to improving the bonding strength between the conductive slurry layer and the current collector, but it is also beneficial to improving the production efficiency of the battery plate.
[0056] Further, in step C, the thickness of the hydrophobic layer is 0.001 to 0.01 mm.
[0057] By limiting the thickness of the hydrophobic layer, it is helpful to ensure the performance of the battery plate at a lower cost.
[0058] A hydrophobic battery plate is prepared using the above-mentioned method for preparing the hydrophobic battery plate.
[0059] This scheme also proposes a hydrophobic battery plate, which is beneficial to improving the bonding strength between the conductive slurry layer and the current collector, thereby solving problems such as voltage drop, short circuit and shortened cycle life that occur during the use of the battery, and has good application prospects.
[0060] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0061] Example 1
[0062] A. 5% nickelous hydroxide, 20% conductive carbon black and 69% N-methylpyrrolidone are stirred evenly to obtain a first mixture; 6% PTFE binder is added to the first mixture, stirred and filtered with a 20-mesh filter to obtain a conductive slurry; wherein the manufacturer of the PTFE binder is Shanghai Huayi Sanaifu New Materials Co., Ltd., and the model is PR301B.
[0063] B. Fill the conductive slurry into the current collector with a porous structure, and perform rapid drying, slow drying and compaction in sequence to obtain a conductive slurry layer with a thickness of 0.5 mm; wherein, the drying temperature of the rapid drying is 180°C, and the drying time is 10 s; the drying time of the slow drying is 140°C, and the drying time is 20 s; the compaction pressure is 300T, and the time is 10 s.
[0064] C. PTFE adhesive was coated on the surface of the conductive paste layer, and after drying at 185° C. for 20 seconds, a hydrophobic layer with a thickness of 0.005 mm was formed to obtain a hydrophobic battery plate.
[0065] The hydrophobic battery plate obtained in Example 1 was cut into 200 cm 2 , obtain test sample 1, spray water on the surface of test sample 1, and visually observe the number of water droplets on the surface of test sample 1. The result shows that the number of water droplets on the surface of test sample 1 is 4, which meets the requirement of water droplet number ≤ 5 / 200cm 2, indicating that the hydrophobicity of the product in Example 1 meets the requirements.
[0066] The hydrophobic battery plate obtained in Example 1 was subjected to a charge and discharge test according to the requirements of Table 1 below. During the test, the charge and discharge performance was normal, and after the test, the conductive slurry layer was still firmly adhered to the surface of the current collector, indicating that the hydrophobic battery plate prepared in Example 1 is beneficial to improving the bonding strength between the conductive slurry layer and the current collector.
[0067] Table 1 Hydrophobic battery plate charge and discharge test method
[0068]
[0069] Example 2
[0070] A. 8% nickel hydroxide, 23% conductive carbon black and 65% pine alcohol are uniformly stirred to obtain a first mixture; 4% PTFE binder is added to the first mixture, stirred and filtered with a 30-mesh filter to obtain a conductive slurry; wherein the manufacturer of the PTFE binder is Shanghai Huayi Sanaifu New Materials Co., Ltd., and the model is PR301B.
[0071] B. Fill the conductive slurry into the current collector with a porous structure, and perform rapid drying, slow drying and compaction in sequence to obtain a conductive slurry layer with a thickness of 0.4 mm; wherein, the drying temperature of the rapid drying is 170°C, and the drying time is 10 s; the drying time of the slow drying is 140°C, and the drying time is 20 s; the compaction pressure is 250T, and the time is 8 s.
[0072] C. PTFE adhesive was coated on the surface of the conductive paste layer, and after drying at 185° C. for 30 seconds, a hydrophobic layer with a thickness of 0.003 mm was formed to obtain a hydrophobic battery plate.
[0073] The hydrophobic battery plate obtained in Example 2 was cut into 200 cm 2 , obtain test sample 2, spray water on the surface of test sample 2, and visually observe the number of water droplets on the surface of test sample 2. The result shows that the number of water droplets on the surface of test sample 2 is 3, which meets the requirement of water droplet number ≤ 5 / 200cm 2 , indicating that the hydrophobicity of the product in Example 2 meets the requirements.
[0074] The hydrophobic battery plate obtained in Example 2 was subjected to a charge and discharge test according to the requirements of Table 1. During the test, the charge and discharge performance was normal, and after the test, the conductive slurry layer was still firmly adhered to the surface of the current collector, indicating that the hydrophobic battery plate prepared in Example 2 is beneficial to improving the bonding strength between the conductive slurry layer and the current collector.
[0075] Example 3
[0076] A. 7% nickel hydroxide, 24% conductive carbon black and 65% ethylene carbonate are uniformly stirred to obtain a first mixture; 4% PTFE binder is added to the first mixture, stirred and filtered with a 60-mesh filter to obtain a conductive slurry; wherein the manufacturer of the PTFE binder is Shanghai Huayi Sanaifu New Materials Co., Ltd., and the model is PR301B.
[0077] B. Fill the conductive slurry into the current collector with a porous structure, and perform rapid drying, slow drying and compaction in sequence to obtain a conductive slurry layer with a thickness of 0.5 mm; wherein the drying temperature of the rapid drying is 160°C, and the drying time is 15 s; the drying time of the slow drying is 140°C, and the drying time is 40 s; the compaction pressure is 400T, and the time is 5 s.
[0078] C. PTFE adhesive was coated on the surface of the conductive paste layer, and after drying at 170° C. for 20 seconds, a hydrophobic layer with a thickness of 0.003 mm was formed to obtain a hydrophobic battery plate.
[0079] The hydrophobic battery plate obtained in Example 3 was cut into 200 cm 2 , test sample 3 was obtained, water was sprayed on the surface of test sample 3, and the number of water droplets on the surface of test sample 3 was visually observed. The result showed that the number of water droplets on the surface of test sample 3 was 4, which met the requirement that the number of water droplets was ≤5 / 200cm 2 , indicating that the hydrophobicity of the product in Example 3 meets the requirements.
[0080] The hydrophobic battery plate obtained in Example 3 was subjected to a charge and discharge test according to the requirements of Table 1. During the test, the charge and discharge performance was normal, and after the test, the conductive slurry layer was still firmly adhered to the surface of the current collector, indicating that the hydrophobic battery plate prepared in Example 3 is beneficial to improving the bonding strength between the conductive slurry layer and the current collector.
[0081] Comparative Example 1
[0082] The preparation method and raw materials of Comparative Example 1 are the same as those of Example 1, except that PVDF binder is used in Comparative Example 1. The manufacturer of PVDF binder is Zhejiang Funolin Chemical New Materials Co., Ltd., and the model is FL2300.
[0083] The hydrophobic battery plate obtained in Comparative Example 1 was cut into 200 cm 2 , test sample 4 was obtained, water was sprayed on the surface of test sample 4, and the number of water droplets on the surface of test sample 4 was visually observed. The result showed that the number of water droplets on the surface of test sample 4 was 8, which did not meet the requirement of the number of water droplets ≤ 5 / 200cm 2 , indicating that the hydrophobicity of the product in Comparative Example 1 does not meet the requirements.
[0084] The hydrophobic battery plate obtained in Comparative Example 1 was subjected to charge and discharge tests according to the requirements of Table 1. During the test, the charge and discharge performance was abnormal, and after the test, the conductive slurry layer fell off from the surface of the current collector, indicating that the hydrophobic battery plate prepared in Comparative Example 1 could not meet the use requirements.
[0085] Comparative Example 2
[0086] The preparation method and raw materials of Comparative Example 2 are the same as those of Example 1, except that step C is missing in Comparative Example 2.
[0087] The hydrophobic battery plate obtained in Comparative Example 2 was cut into 200 cm 2 , test sample 5 was obtained, water was sprayed on the surface of test sample 5, and the number of water droplets on the surface of test sample 5 was visually observed. The result showed that the number of water droplets on the surface of test sample 5 was 9, which did not meet the requirement of the number of water droplets ≤ 5 / 200cm 2 , indicating that the hydrophobicity of the product in Comparative Example 2 does not meet the requirements.
[0088] The hydrophobic battery plate obtained in Comparative Example 2 was subjected to charge and discharge tests according to the requirements of Table 1. During the test, the charge and discharge performance was abnormal, and after the test, the conductive slurry layer fell off from the surface of the current collector, indicating that the hydrophobic battery plate prepared in Comparative Example 2 could not meet the use requirements.
[0089] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.
Claims
1. A method for preparing a hydrophobic battery plate, characterized in that: The following steps are involved: A. stirring the active material, the conductive agent and the solvent to obtain a first mixture; adding a PTFE binder to the first mixture, stirring and filtering to obtain a conductive slurry; B. filling the conductive slurry into a current collector having a porous structure, and then drying and compacting the current collector to obtain a conductive slurry layer; C. Coating a PTFE binder on the surface of the conductive slurry layer, and forming a hydrophobic layer after drying to obtain a hydrophobic battery plate.
2. The method for preparing a hydrophobic battery plate according to claim 1, characterized in that: In step A, the content of the PTFE binder in the conductive paste is 1-7% calculated by mass percentage.
3. The method for preparing a hydrophobic battery plate according to claim 1, characterized in that: In step A, the mesh size of the filtration is 20 to 60 meshes.
4. The method for preparing a hydrophobic battery plate according to claim 1, characterized in that: Step B specifically comprises: filling the conductive slurry into a current collector having a porous structure, and sequentially performing rapid drying, slow drying and compacting to obtain a conductive slurry layer; The drying temperature of the rapid drying is 160-180°C, and the drying time is 10-15s; The drying temperature of the slow drying is 140-155° C., and the drying time is 20-40 seconds; The compaction pressure is 210-400T, and the time is 5-10s.
5. The method for preparing a hydrophobic battery plate according to claim 1, characterized in that: In step B, the thickness of the conductive paste layer is 0.4-0.6 mm.
6. The method for preparing a hydrophobic battery plate according to claim 1, characterized in that: In step B, the current collector having a porous structure is any one of a foam nickel substrate, a honeycomb nickel substrate and a copper foam substrate.
7. The method for preparing a hydrophobic battery plate according to claim 1, characterized in that: In step C, the drying temperature is 170-185° C., and the drying time is 20-35 seconds.
8. The method for preparing a hydrophobic battery plate according to claim 1, characterized in that: In step C, the thickness of the hydrophobic layer is 0.001 to 0.01 mm.
9. A hydrophobic battery plate, characterized in that: The hydrophobic battery plate is prepared using the method for preparing the hydrophobic battery plate according to any one of claims 1 to 8.